FRI0396 Double-blind comparison of mycophenolate mofetil and oral cyclophosphamide for treatment of scleroderma-related interstitial lung disease (scleroderma lung study [SLS] II): rationale, design, methods, baseline characteristics and patient disposition. (23rd January 2014) - Khanna, D.; Roth, M.; Furst, D.; Clements, P.; Goldin, J.; Arriola, E.; Kotlerman, J.; Tseng, C.-H.; Kim, G.; Elashoff, R.; Tashkin, D.; ,
Abstract : Background: Cyclophosphamide (CYC), is the only therapy that has been shown thus far to be efficacious in scleroderma-related interstitial lung disease (SSc-ILD). However, the utility of CYC is constrained by its toxicity, which limits treatment to only ≤1 year. Findings from several uncontrolled studies in small numbers of patients with SSc-ILD (n≤17) suggest that mycophenolate mofetil (MMF) is a safe and effective treatment for SSc-ILD. Methods: SLS II is a double-blind, double-dummy, parallel-group randomized controlled trial (DB DD PG RCT) comparing the efficacy and safety of MMF (titrated to 3 g/d over 2 years) versus oral CYC (titrated to 2 mg/kg/d for 1 year followed by placebo for another year) in patients with active SSc-ILD (target enrollment 150 patients). Key eligibility criteria included adults, ≤ 7 yrs, any ground glass opacity (GGO) as an indication of "active" disease, and FVC% between 40-80% predicted. Procedures : Spirometry, lung volumes, DLCO, SGRQ, SF-12, modified Rodnan skin score (mRSS), and cough questionnaire at screening and/or baseline and every 3 months for 2 yrs; BDI (baseline); TDI every 3 months for 2 yrs; HRCT (screening and 2 years ;central reading center); toxicity monitoring. Statistical analysis : Primary endpoints: FVC % pred at 2 yrs, adjusted for baseline FVC % pred and "fibrosis" score on screening HRCT and toxicity outcomes over 2 yrs. Results: Baseline results are presented in Table 1 . Premature discontinuation of study drug (38/130) – due to drug toxicity (13/38); failure to return for 24-month visits (12/26 due); SAEs (38) – 5 felt to be study-related; 1/130 treatment failure (defined by 15% pred decrease in FVC sustained for ≥1 mo). Conclusions: A DB DD RCT of oral CYC for 1 yr versus MMF for 2 yrs in patients with progressive SSc-ILD is feasible with a low rate (10%) of discontinuations due to drug toxicity overall. Extent of ILD on HRCT is significantly, albeit modestly, correlated with physiologic impairment, supporting the use of change in HRCT scores from baseline as a key endpoint. Disclosure of Interest : None Declared